The design of Digital UART by using VHDL - Norhuzaimin, Julai; Lio Siang Peng, John; Kismet, Hong Ping (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 18th - 19th May 2005 at Putra Palace Hotel, Kangar.